SISTEM INFORMASI MANAJEMEN PADA TOKO GROSIR AL-FATTAH BERBASIS WEB - Nur Khisanah, Isnaini Intan; Fatmawati, Azizah (LPPM Unbaja, 2024)
This research addresses management challenges encountered by Al-Fattah wholesale store in Boyolali, specifically in stock management, financial analysis, and profit calculations, resulting in supply and financial gaps. To tackle these issues, a web-based Management Information System (MIS) was developed using the Rapid Application Development (RAD) approach. The development process involved requirements planning, design workshops, and implementation using PHP integrated with MySQL. The MIS aims to enhance inventory reporting, accurate profit calculations, and structured sales transaction recording to streamline operations and facilitate decision-making at Al-Fattah. Post-implementation, rigorous testing, including System Usability Scale (SUS) assessment on 30 respondents, yielded an average score of 80, categorizing usability as